KADAR GLUKOSA PADA SERUM LIPEMIK DENGAN PENGGUNAAN POLYETHYLENE GLYCOL 6000 8% DAN HIGH SPEED SENTRIFUGASI - Martha Atik Martsiningsih; Sujono Sujono; Bambang Supriyanta; Menik Kasiyati; Catherine Surya; Budi Martono; Budi Setiawan (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Bacground: Lipemic serum is a problem in many laboratories because it can cause the results of glucose levels in the serum to be falsely high. The examination uses a photometric method, which can cause interference with wave lengths and light scattering. As an alternative to high-speed centrifugation to remove lipemic serum, another method for handling lipemic serum is precipitation, which is carried out by processing polyethylene glycol 6000 8%.Aims: This research wants to know the differences in the handling of lipemic serum before and after being processed using polyethlyene glycol 6000 8% and high-speed centrifugation.Method: This type of research is an experiment with Static Group Comparison. Research conducted at the Clinical Pathology Laboratory Installation at the Gadjah Mada University Academic Hospital in November 2022. The sample of this study was lipemic serum with a total of twenty samples obtained from the rest of the examination in two Clinical Laboratory Installations Hospitals in Yogyakarta. Research data were analyzed using the Paired T-Test and Independent T-Test. Result: The statistical analysis (p = 0.000) 0.05 revealed that there is a difference in lipemic serum glucose levels before and after PEG 6000 8% processing and high-speed centrifugation. Before processing with polyethylene glycol 6000 8% and high-speed centrifugation, the average yield of glucose levels in lipemic serum was 116.3 mg/dl. The average glucose level before and after PEG 6000 8% processing was 108.65 mg/dl. Before and after high-speed centrifugation, the average glucose level was 114.1 mg/dl.Conclusion: Overall, both the PEG 6000 8% processing and the high-speed centrifugation resulted in a significant decrease in lipemic serum glucose levels. These methods appear to be effective in reducing the interference caused by lipemia and improving the accuracy of glucose measurements in the serum.